Risks of sexually transmitted infection in sex workers in Teresina-PI (Research, Society and Development, 2020)
In Brazil, the prostitution has been considered a professional category by the Ministry of Labor and Employment since 2002, and is linked to associations in several Brazilian states, but it isn`t regulated. It is a stigmatized activity and exposed to various risk factors such as alcohol consumption, tobacco, illicit drugs, violence, sexual exploration and sexually transmitted infections. The objective of the study was to know the socio-demographic data and the STIs of the sex workers in Teresina-PI. It is a quantitative descriptive study with 96 female sex workers registered and regularized in the Association of Prostitutes of Piauí. The data collection was in the places of the workers, such as bars, nightclubs, bordellos/cabaret, using a closed questionnaire. The data was organized into Microsoft Office Excel spreadsheets and transferred to the SPSS Program. The majority part of sex workers was young women between the ages of 25 and 31 (34.4%), single women (77.1%), average schooling (46.9%), brown women (58.3%), to a minimum wage (52.1%), fixed residence (58.3%) and had children (78.1%). The age group was 15 to 25 years old (71.9%), with a time of 2 to 5 years (49.0%), bars were the most frequented places (49, 0%), performing 4 to 5 programs daily (47.9%), having the most practiced vaginal sex (56.3%). As for STIs, candidiasis (25.0%), painful symptoms when urinating (69.8%), and abortions (50%) were found. In view of the data, it is considered necessary to increase the assistance coverage for Basic Health Care with strategies of prevention, promotion and protection to reduce the health problems of sex workers.